2023
DOI: 10.1186/s12913-023-09869-8
|View full text |Cite
|
Sign up to set email alerts
|

Quality communication can improve patient-centred health outcomes among older patients: a rapid review

Samer H. Sharkiya

Abstract: Background Effective communication is a cornerstone of quality healthcare. Communication helps providers bond with patients, forming therapeutic relationships that benefit patient-centred outcomes. The information exchanged between the provider and patient can help in medical decision-making, such as better self-management. This rapid review investigated the effects of quality and effective communication on patient-centred outcomes among older patients. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…From an individual perspective, this study revealed significant relationships between medical risk perception, negative emotions, and patient satisfaction. Initially, we observed that medical risk perception positively influences patient satisfaction (H1), corroborating the findings of Jordão et al (2020) and Sharkiya (2023) . This link can be attributed to the alignment between patients’ expectations of treatment outcomes and actual results.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…From an individual perspective, this study revealed significant relationships between medical risk perception, negative emotions, and patient satisfaction. Initially, we observed that medical risk perception positively influences patient satisfaction (H1), corroborating the findings of Jordão et al (2020) and Sharkiya (2023) . This link can be attributed to the alignment between patients’ expectations of treatment outcomes and actual results.…”
Section: Discussionsupporting
confidence: 83%
“… Ozdemir and Finkelstein (2018) found that patients with a high level of risk perception were more inclined to actively participate in medical decision-making, which increased their satisfaction with and trust in the treatment plan. Similarly, Sharkiya (2023) discovered that detailed discussions of treatment risks and benefits could enhance patient acceptance of and satisfaction with treatment plans. Moreover, Frosch et al (2003) found that patients with hypertension, when well informed about the risks involved in decision-making, are more likely to follow medical advice, thereby leading to better long-term blood pressure control, improved health outcomes, and increased satisfaction.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…By incorporating PMR into the medical curriculum and encouraging its practice among healthcare professionals, there is an opportunity to significantly enhance the quality of interpersonal interactions across various aspects of medical practice. This, in turn, can lead to improved patient outcomes, more cohesive healthcare teams, and a more supportive educational environment (Sharkiya, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare providers need to open up empathetic communication channels, ensuring that patients feel heard and understood at every step of their care. By building strong relationships between patients and healthcare providers, it is expected that positive attitudes towards the reuse of outpatient services can be enhanced, supporting efforts towards better health for the community at large (16).…”
Section: The Influence Of Attitudes On the Reuse Of Outpatient Servicesmentioning
confidence: 99%